A quick review of ethics, design thinking, gender, and AI development. Issue 1 (2nd January 2023) - Kronqvist, Aila; Rousi, Rebekah Ann
ABSTRACT: Ethics, artificial intelligence (AI), and design thinking are current buzz words. The threat of bias-riddled machine learning algorithms is represented media-wide. Research and development initiatives are endeavoring to 'translate' ethics into processes and machine logic and design thinking as a method is adopted to gauge the interests and values of a vast range of stakeholders. Gender, its framing, reflection, and critical evaluation in relation to design thinking as a means for developing ethical AI appear to be less represented in scholarly discourse. Against a background of critical theory and gender studies that describe and problematize gender, its construction and norms in socio-technological discourse, the authors of this article aim to generate insight into the current state of gender in design thinking research focused on ethics and AI. A review of scholarly articles revealed trends in popularity of concepts and prominence in the application of design thinking in specific fields (i.e., educational research). Repetition characterizes the more challenging topics or wicked problems. Provocation and investigation of gender from the perspectives of practitioners, creativity, and its influence in design thinking seem all but visible.